Niat Melakukan Islamic Online Donation Pada Generasi Z: Peran Attitude Sebagai Mediator Pada Model UTAUT-3 - Puspawati, Dewita; Abas, Novel Idris; Ariani, Kurnia Rina (Universitas Muhammadiyah Malang, 2024)
Purpose: This study aims to examine the effect of the UTAUT-3 model, namely performance expectancy, habit, and personal innovativeness on the intention to make Islamic online donations mediated by attitude in generation Z. Methodology/ approach: This study uses a survey method by distributing questionnaires online. The sample in this study were 180 respondents. We use SEM-PLS to analyze data. Findings: The results show that performance expectancy and personal innovativeness affect attitude, while habit does not affect. The intention to do Islamic online donation is influenced by performance expectancy, habit, personal innovativeness, and attitude. Attitude can mediate the relationship between performance expectancy and personal innovativeness with the intention to pay ZIS online. However, the effect of habit on online ZIS payment intentions cannot be mediated by attitude. Practical implications: As Generation Z dominates the population in Indonesia, this generation has high potential in ZIS collection. ZIS Institutions can further promote the convenience of online ZIS payments. Originality/value: This study uses personal innovativeness as a construct of UTAUT-3 in the intention to Islamic online donation.